Ruins and Imperial Legacies: Global Geographies of Portuguese-built Forts - Sarmento, João Carlos Vicente (2011)
This book, encouraged by the new debates that the postcolonial turn promoted concerning questions of ‘geography, colonialism and postcolonialism’ (Power,Mohan and Mercer 2006: 231), takes a critical look at this evolving situation. I am concerned with material heritage, with ‘dissect[ing] post-colonialism as threaded through real spaces, built forms and the material substance of everyday biospheres’ (Yeoh 2009: 562), and involved in the re-materialisation proposals that emerged in Cultural Geography in the past years (Driver 1996).